Characterization of the Blood Bacterial Microbiota in Lowland Tapirs (Tapirus terrestris), a Vulnerable Species in Brazil - Anna Claudia Baumel Mongruel; Emília Patrícia Medici; Rosangela Zacarias Machado; Keith Clay; Marcos Rogério André (Microorganisms)
Microbiome studies targeting hypervariable regions of the 16S rRNA gene are suitable for understanding interactions between animals and their associated bacteria. While many studies focus on the gut microbiome, assessments of blood microbiota remain scarce despite the prevalence of blood-borne pathogens in vertebrates. This study aimed to investigate the bacterial community in blood samples from 79 living and 7 road-killed lowland tapirs (Tapirus terrestris), a vulnerable species, sampled in two biomes in midwestern Brazil: Pantanal and Cerrado. Animals were categorized by condition (living or road-killed), sex, age, and biome. V3–V4 16S rRNA fragments were obtained from 86 blood samples and 4 negative controls. After filtering contaminants, 13,742,198 sequences representing 2146 ASVs were analyzed. Alpha diversity significantly differed by condition, while beta diversity differed by condition, site, and age (adults vs. sub-adults). For living animals (79/86 samples), alpha diversity showed no significant differences, but beta diversity differed by age. Different vector-borne bacterial pathogens, including Anaplasmataceae, Bartonella, and Borrelia spp., were detected. Additionally, evidence of transient translocation of microbial communities from other body regions to the bloodstream was observed. Amplification of bacterial 16S rRNA from blood samples of wild T. terrestris provided novel information about the diversity of blood-borne microbiota of lowland tapirs, members of a poorly studied mammalian family. Next-generation sequencing proved to be a valuable tool for screening potential vector-borne pathogens in this host.